Ethics of religious belief - Sykes, R; Sykes, Robert Arthur Roderick (1979)
﻿ This thesis seeks to answer the question of what it would be for a person to be persuaded rationally to believe that God exists, and tries to explain in a related way the possibility of rationality in Christian faith. I begin by explicating and defending the "ethics of belief" approach to epistemology. Then two competing ethics of belief are described: "Strong Formalism", which holds, through a voluntaristic decision, a deductivist epistemology; and "Soft Rationalism", which contains an infonnalist epistemology, and rejects voluntarism. Arguments for and against each view are canvassed. But I show that our attempted adjudication is blocked by the "Ultimate Rationality Problem": no ethic of belief seems able rationally to justify its view of rationality. I reduce the Problem to this fact: any view of rationality refutes itself which tries to give a foundational method of epistemic evaluation that both gives a verdict on every proposition and avoids self-justification. I reject several suggested solutions in favour of one which replaces the foundational view of justification by a contextual view. I then generate from the process of justification itself several common epistemic standards, which allow us rationally to favour Soft Rationalism over Strong Formalism. But the former is both foundationalist and needlessly opposed to formalism. I remedy these faults by developing a "Modest Formalist" ethic of belief: a'partly formal set of standards for rational metaphysical argument,"given in. the form of a set of constitutive rules for certain games of interpretive argument. In doing this I defend an improved theory of epistemic probability, and reveal the structure of our substantive views of rationality - as this virtue would be required of believings per se, of actions based on believings, and'of actions (such as living a Christian life) based on what I describe as "experimental faith".